The Effect of Skills Education on The Self-Study Capability of New Students Universitas Terbuka - Suwardika, Gede; Hariati Sawitri, Hendrin (Journal of Education Reseach and Evaluation, 2019)
The purpose of this study is to observe the Impact of the Independent Learning  Skills Education on the Self-Learning Readiness of New Students by 2018. We use the Analysis Path to observe the Student’s Self-Learning Readiness consisting of time management skills, effective module reading, recording of reading skills, tutorial, and skill of accessing service on line. The Results suggest that Skills Education is an important factor affecting their study in the future